The Effect of Financial Targets, Financial Stability, and Ineffective Monitoring on Financial Statement Fraud in Indonesian Manufacturing Companies (2020–2023) - M. Abdul Malik Kholidin; Febrian Kwarto (Journal of World Science, 2025)
This study aims to analyze the influence of financial targets, financial stability, and ineffective supervision on financial statement fraud in manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2023 period. Financial statement fraud was measured using the Beneish M-Score, while independent variables were proxied with Return on Assets (ROA), asset change (ACHANGE), and proportion of independent board of commissioners (BDOUT). The research sample included 88 companies with a total of 352 panel data observations. Data analysis was performed using panel data regression with a random effects (REM) approach through the EViews 13 software. The results showed that financial targets played a significant role in encouraging the fraudulent practice of financial statements, while financial stability and ineffectiveness of supervision were not proven to have a strong influence. These findings confirm that the pressure to achieve profit performance is still the dominant factor in triggering fraud in Indonesia's manufacturing sector, while the effectiveness of formal supervision has not been consistent. The theoretical contribution of this research is to strengthen the pressure dimension in Fraud Hexagon Theory while weakening the empirical evidence on the opportunity dimension. The practical contribution of this research is to provide guidance for auditors, regulators, and management to improve the effectiveness of supervision through forensic audits and strengthening the competence of independent board of commissioners.